Exploring the efficacy of forum theatre and online high-fidelity simulation to challenge unconscious bias (Journal of Applied Learning and Teaching, 2024)
There is an ongoing commitment within nursing curricula to ensure that student nurses are fully prepared to support a person with an intellectual disability. In response to COVID-19 restrictions, universities rapidly adapted to digital technologies to continue the delivery of nurse education. The aim of this research study was to evaluate the effectiveness of an online educational initiative – Digital Community Health Awareness Training (DCHAT) – in comparison to attending the face-to-face version of CHAT. This research study adopted a two-phase qualitative approach using questionnaires to discern the knowledge of participants prior to and after attending a DCHAT workshop. The workshop was facilitated by actors with an intellectual disability using forum theatre. Open and closed questions were analysed using thematic analysis.The findings revealed that engaging in the online workshop increased participants’ knowledge and skills. This was in aspects of supporting people with intellectual disabilities in health as well as an increased understanding of unconscious bias. Additionally, this research found that following the DCHAT workshop, relationships developed from passive learners to friends and compatriots. This study found that delivering DCHAT was effective and appropriate in preparing student nurses to support people with intellectual disabilities. The implications of the findings suggest that the DCHAT can be delivered by actors assuming the role of patients with intellectual disabilities to global audiences.